Ecosystem services of wetlands in the upper Abbay River Basin, Ethiopia - Fentaw, G.; Beneberu, G.; Wondie, A.; Eneyew, B. G. (Elsevier, 2025)
Wetlands are among the most important and productive ecosystems, offering both ecological and socioeconomic benefits. It is essential to understand the ecosystem services (ESs) offered by wetlands for their efficient conservation and sustainable use. Ethiopia has a lot of wetland resources, but little is known about their ESs. Therefore, the purpose of this study was to assess the ESs provided by six (Geray, Gudera, Infranze, Kurt_Bahir, Wonjeta and Zindib) wetlands in the upper Abbay River basin, Ethiopia.The data were collected from 377 household heads through face-to-face interviews using 4-point Likert-type scale question items. Rapid assessment of wetland ecosystem service (RAWES) approach was applied to triangulate the data collected through cross-sectional household survey. Descriptive statistics was applied to analyze household survey and the RAWES data. Kruskal-Wallis test was used to analyze the differences among the ESs provided by the wetlands whereas; Mann-Whitney U test was used to analyze the difference between the mean score of survey and RAWES data. The findings of both the RAWES and the survey data revealed that the wetlands provide various provisioning services; particularly water for livestock, other domestic purposes and irrigation crop production, livestock fodder and seedling raising. The importance of all the wetlands in delivering these provisioning services was not similar. As confirmed by Kruskal-Wallis test, the differences among the six wetlands were statistically significant (p < 0.05). Infranze wetland was found to be the most important wetland whereas Zindib wetland was the least. The importance of the wetlands in providing regulating, cultural and supporting services was recognized by significant number of respondent; although most of them rated the delivery of these ESs as ‘low’. The views of participants of RAWES on the contribution of the wetlands to regulating, cultural and supporting services, however, were different from the respondents’ views. Mann-Whitney U test confirmed that the differences are statistically significant. This indicated that the respondents had low understanding towards these ESs of the wetlands may be due to their low educational level. Therefore, increasing the society’s awareness towards the non-material benefits of the wetlands is crucial for their sustainable utilization.